2016
DOI: 10.12968/jowc.2016.25.9.544
|View full text |Cite
|
Sign up to set email alerts
|

Honey for wound care in the 21st century

Abstract: This review is written in memory of Professor Peter Molan, who published a paper in the Journal of Wound Care in 1999 describing the therapeutic properties of honey in relation to wound care. It provides an update to show how our understanding of the mode of action of honey has changed within the past 17 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 102 publications
1
33
0
Order By: Relevance
“…The literature includes reports on numerous honeys, from different floral sources, for in vitro antimicrobial activity in particular. Due to the pioneering work of the late Peter Molan 3 in New Zealand over the past 25 years, it has emerged that of the range of honeys tested, those from one source, manuka, has particularly high antimicrobial activity. 4 Subsequently many other reports have supported and clarified this activity this is summarised in a review by Carter et al 5 It is owing to a series of seminal articles by Molan 6 and colleagues 7,8 in 1999 that the modern approach to honey in wound can be traced.…”
Section: Biological Research Into Honeymentioning
confidence: 99%
See 1 more Smart Citation
“…The literature includes reports on numerous honeys, from different floral sources, for in vitro antimicrobial activity in particular. Due to the pioneering work of the late Peter Molan 3 in New Zealand over the past 25 years, it has emerged that of the range of honeys tested, those from one source, manuka, has particularly high antimicrobial activity. 4 Subsequently many other reports have supported and clarified this activity this is summarised in a review by Carter et al 5 It is owing to a series of seminal articles by Molan 6 and colleagues 7,8 in 1999 that the modern approach to honey in wound can be traced.…”
Section: Biological Research Into Honeymentioning
confidence: 99%
“…13,26 This aspect of manuka action has recently been examined using 83 clinical isolates of six genera of wound pathogens. 3,27 The study involved measurement of both minimum inhibitory concentrations (MICs) and minimum bactericidal concentrations (MBCs) and electron microscopy for evidence of cell lysis. The authors concluded that 'the findings provide optimism that topical manuka honey might have a role to play in limiting multidrug resistant Gram-negative bacteria'.…”
Section: Antimicrobial Actionmentioning
confidence: 99%
“…The chemical composition of honey makes it a complex natural mixture of chemical compounds allowing it to show important biological properties, such as the ability to promote wound healing [ 2 ] and its antimicrobial, anti-inflammatory, and antioxidant capacity [ 3 ]. The antioxidant and antimicrobial capacity of honey has been one of the biological properties most studied in honey and has been closely associated with its floral origin [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The development of wound care products including honey is continuing rapidly. It is used in wound dressings or in tube form for wound treatments [7,8]. Manuka honey is scientifically recognized for its antimicrobial and wound healing properties and is now used in topical treatment of wound infections in clinics [17].…”
Section: Groupmentioning
confidence: 99%
“…Honey has antibacterial effect and many other therapeutic properties supporting healing [4,7,8]. Honey creates a cleansing effect on the wound and debride the necrotic tissue.…”
Section: Introductionmentioning
confidence: 99%